ETHNO-VETERINARY PRACTICES AMONGST SMALL–HOLDER FARMERS IN EKITI STATE, NIGERIA - Kolawole, O. D.; Okorie, V. O.; Ogidiowa, M. T.; Adeogun, M. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
This paper aimed at identifying factors influencing the use of ethno-veterinary practices amongst goat and poultry farmers in Ekiti state, Nigeria. It specifically described the socio-economic characteristics of the farmers; identified some diseases of goats and poultry with their corresponding indigenous cures; presented the procedures used in developing some of the ethno-veterinary medicine amongst farmers; identified the reasons for using ethno-veterinary practices; analysed the ecological factors influencing ethno-veterinary practices; identified the roles played by institutions in the utilisation of ethno-veterinary practices; and examined the benefits and problems associated with ethno-veterinary practices in Ekiti State, Nigeria. A multi-stage sampling procedure was used to select 100 respondents from ten communities, namely: Otun-Ekiti, Igogo-Ekiti, Osin-Ekiti, Omuo-Ekiti, Ilasa-Ekiti, Araromi-Ekiti, Efon-Alaaye, Oba-Ayetoro, Ise-Ekiti, and Orun-Ekiti. Pre-tested structured and unstructured interview schedules were used to collect quantitative data, while Focused Group Discussions (FGDs) were used to elicit qualitative data from the respondents. Frequency distribution, percentages, means and standard deviation were used to describe the data. Inferential statistics such as correlation and Chi-Square analyses were used to make deductions. The correlation result showed that at p < 0.05 level of significance, age (r = 0.368), family size (r = 0.114) and association membership (r = 0.231) were positively and significantly correlated with the utilisation of ethno-veterinary practices while education level (r - 0.342), farming scope (r = -0.261,) and cosmopoliteness (-0.135) had negative but significant correlation with the utilisation of ethno-veterinary practices. Some of the problems (associated with the use of indigenous knowledge) identified by the farmers were lack of institutional support and the seasonal nature of some medicinal plants. It is, thus, suggested that all identified constraints need be removed by government to enhance the use of low-external inputs for sustainable agricultural development.